Improving undergraduate astronomy students' skills with research literature via accessible summaries: an exploratory case study with Astrobites-based reading assignments - Lewis, Briley; Waggoner, Abygail R.; Clarke, Emma; Crisp, Alison L.; Dodici, Mark; Doskoch, Graham M.; Foley, Michael M.; Golant, Ryan; Grayson, Skylar; Hegde, Sahil; Korhonen Cuestas, Nathalie; Law, Charles J.; et al. (Physical review. Physics education research, 2025)
Undergraduate physics and astronomy students are expected to engage with scientific literature as they begin their research careers, yet reading comprehension skills are rarely explicitly taught in major courses. We seek to determine the efficacy of a reading assignment designed to improve undergraduate astronomy (or related) majors’ perceived ability to engage with research literature by using accessible summaries of current research written by experts in the field. During the 2022-2023 academic year, faculty members from six institutions incorporated reading assignments using accessible summaries from Astrobites into their undergraduate astronomy major courses, surveyed their students before and after the activities, and participated in follow-up interviews with our research team. Quantitative and qualitative survey data from 52 students show that students’ perceptions of their abilities to understand jargon and identify the main takeaways of a paper significantly improved with the use of the tested assignment template. Additionally, students reported increased confidence in their abilities within astronomy after exposure to these assignments, and instructors having valued a ready-to-use resource for incorporating reading comprehension into their pedagogy. This exploratory case study, using Astrobites-based assignments, suggests that incorporating current research into the undergraduate classroom through accessible literature summaries may increase students’ confidence and ability to engage with research literature, thereby assisting in their preparation for participation in research careers.